2020
DOI: 10.1111/scs.12827
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with risk of care dependency in disabled geriatric patients

Abstract: Factors associated with risk of care dependency in disabled geriatric patients Introduction: The growing number of elderly people results in the intensification of disability, reduced level of independency and quality of life as well as augmented demand on medical and social services. The aim of the study was to identify factors associated with probability of care dependency in disabled geriatric patients. Materials and methods: The study involved 200 patients aged 60 or over, consecutively admitted to the Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
6
0
4
Order By: Relevance
“…The strong association between ADL dependence and cognitive impairment we found supports and extends the previous literature reporting similar findings [ 16 , 20 , 31 , 32 , 33 ]. However, these previous studies differed in population and study designs: patients with dementia in all kinds of disease stages and elderly people living in nursing homes were studied in both cross-sectional and longitudinal designs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The strong association between ADL dependence and cognitive impairment we found supports and extends the previous literature reporting similar findings [ 16 , 20 , 31 , 32 , 33 ]. However, these previous studies differed in population and study designs: patients with dementia in all kinds of disease stages and elderly people living in nursing homes were studied in both cross-sectional and longitudinal designs.…”
Section: Discussionsupporting
confidence: 92%
“…It is also somewhat surprising that in our study we found a significant association between female gender and increased ADL dependence, since in previous studies regarding factors associated with ADL dependence, “gender” was not found to be significantly associated. Yet these studies were conducted on community-dwelling elderly, patients with dementia, and elderly care [ 16 , 20 , 21 , 31 ]. On the other hand, a large cross-national study comparing sex differences in ADL in Europe has found that women are more likely to be ADL dependent than men and that this difference increases with age [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially adults aged 80 years and older can be a vulnerable group regarding perceived negative attitudes or ageism [5], because these individuals are often stereotyped as being frail and dependent [6] and have a higher risk of care dependency [7]. People in this age group are also referred to as people in the so‐called fourth age [8], which is not defined by their chronological age, but is described as a loss of the ability to manage tasks of daily living.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…The Care Dependency Scale (CDS) was designed to assess the multidimensional care dependency of older people in their daily living environment, and it is recommended across Europe. The scale has also been adapted to Polish conditions [ 5 , 6 , 7 , 8 ]. The scale was developed following Virginia Henderson’s theory of nursing and includes both physical and psychosocial aspects, which are used to assess care dependency [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%